Internet of Things : usage and application - Ayop, Zakiah (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
The main goal of this book is to encourage both researchers and practitioners to share and exchange their experiences and recent studies between academia and industry. The overall objectives are: • To improve the awareness of readers about loT concepts, technologies, and application areas. • To present case-studies and innovative applications of the loT. • To highlight and discuss the recent development and emerging trends in the lot. • To propose new models, practical solutions and technological advances of the lot. • To address implementation issues and challenges.